Extracts of Tagetes patula L. (Asteraceae): a bactericidal potential against Moko - Soto Rueda, Eliana Marcela; Rodríguez Ruiz, Yenni Leandra; Loango Chamorro, Nelsy; Landázuri, Patricia (Revista Mexicana de Ciencias Agrícolas, 2018)
Ralstonia solanacearum race 2 is the cause of Moko or bacterial wilt, producing large economic losses in crops such as banana, tobacco and tomato. Several components of the extracts and essential oil (AE) of Tagetes patula L. have been described, including: benzofurans, carotenoids, flavonoids and thiophenes that are biologically active and potentially allelopathic against many pathogenic organisms. The investigations of the effect of the extracts and the AE of T. patula L., against R. solanacearum are scarce. The objective of this investigation was to analyze the antioxidant potential and determine the effect of the floral methanolic extracts (EMF) and leaves (EMH) and the AE on the growth of the bacteria. The T. patula EMF has a higher free radical scavenging capacity (DPPH) than the AE, possibly related to its higher phenol content. The EMF also has a high content of flavonoids and terpenoids. The chemical composition of the AE was determined by gas/mass chromatography, which revealed six major components, which represent more than 84% of the EA: Indane 5.47%, D-limonene 5.76%, Z-ocimene 5.98%, terpinolene 6.73%, Bervenona 19.98% and piperitone with 40.4%. The EMF as the AE inhibited the growth of R. solanacearum race 2, but the AE was more effective (radius of inhibition 16 cm). Based on these results EMF and AE of flowers and leaves of T. patula may be an option for control R. solanacearum race 2.
Keywords: Ralstonia solanacearum; Tagetes patula L.; antioxidant; essential oil; plant extracts